Bài 6: Phân tích đa thức thành nhân tử bằng phương pháp đặt nhân tử chung

LV

undefinedgiải hết dùm em nha

MH
14 tháng 10 2021 lúc 19:55

a) \(3x\left(x-2\right)-x+2=0\)

\(3x\left(x-2\right)-\left(x-2\right)=0\)

\(\left(x-2\right)\left(3x-1\right)=0\)

\(\left[{}\begin{matrix}x-2=0\\3x-1=0\end{matrix}\right.\)

\(\left[{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\)

b) \(x\left(x-2\right)-2\left(x-2\right)=0\)

\(\left(x-2\right)\left(x-2\right)=0\)

\(\left(x-2\right)^2=0\)

\(x-2=0\)

\(x=2\)

Bình luận (0)